Students’ attitude towards natural sciences - Dwi Agus Kurniawan; Astalini Astalini; Darmaji Darmaji; Ririn Melsayanti (International Journal of Evaluation and Research in Education (IJERE), 2019)
The purpose of research was to investigate students’ attitudes towards natural science in Muaro Jambi, Indonesia. The attitude of the students studied was represented by three indicators, namely the attitude towards the investigation in the Natural Sciences, the adoption of a scientific attitude, and a career interest in the science field. The research was a survey research. The instruments in this study were attitude questionnaires and interview sheets. Data analysis techniques for attitude questionnaires used descriptive statistics while for analyzing interview data using the Miles and Huberman model.The study found students’ good attitudes towards natural science subjects.